2011
DOI: 10.1051/ata/2011123
|View full text |Cite
|
Sign up to set email alerts
|

L’effet du stress oxydant induit par l’acétate de plomb sur le système enzymatique du glutathion chez les rats

Abstract: Résumé -Objectif : Ce travail porte sur l'étude de l'effet toxique de l'acétate de plomb sur l'activité du système de défense de glutathion chez les rats. Méthodes : Cette étude a été réalisée sur 40 rats mâles (Albinos wistar) qui ont été répartis en quatre groupes. Pendant une semaine, trois lots de rats ont été traités par une injection intrapéritonéale (ip) par trois doses différentes d'acétate de plomb (25, 50, 100 mg/kg) de poids corporel; un lot témoin a été traité (ip) uniquement par un soluté isotoniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…At this experimental stage, in the third month of SD, the results of dosage of liver oxidative stress showed an increase in the lipid peroxidation rate (MDA). These results were explained by the auto-oxidation of lipids, which were probably induced by obesity or hyperglycemia or both [34]. In parallel, we noted a slight increase in the antioxidant (GSH) levels in the experimen-tal group compared to controls.…”
Section: Discussionsupporting
confidence: 58%
“…At this experimental stage, in the third month of SD, the results of dosage of liver oxidative stress showed an increase in the lipid peroxidation rate (MDA). These results were explained by the auto-oxidation of lipids, which were probably induced by obesity or hyperglycemia or both [34]. In parallel, we noted a slight increase in the antioxidant (GSH) levels in the experimen-tal group compared to controls.…”
Section: Discussionsupporting
confidence: 58%
“…These results are in keeping with the work of (Thylambal and Saroja, 2004;Abdel Moneim et al, 2011), who have shown that the renal cells are no longer capable of controlling the urinary excretion process, as the kidneys are among the organs most sensitive to lead. In addition, according to the study of Saka et al (2011), the increase of serum urea and creatinine in rats exposed to Pb is due to the degradation of hepatic protein Compounds, whereby the proteins may be broken down into amino acids, and then again into urea and creatinine. In this way, when exposed to serum aminotransferase, these amino acids may be converted into carboxylic compounds such as pyruvic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Cells can defend face several detoxification systems; the most important is that of glutathione which is a tripeptide playing a role at various levels in the fight against oxidative stress [25]. This enzyme system also contains glutathione-S-transferase GST that catalyzes the reaction between reduced glutathione and xenobiotic, forming glutathioneconjugated metabolites [26].…”
Section: Histopathological Observationmentioning
confidence: 99%